A Ferrocenyl‐Backboned Unsymmetric O, C‐Coordinating Ligand and Its Tin Derivatives. Issue 4 (15th June 2016) - Janssen, Bastian; Lutter, Michael; Alnasr, Hazem; Krossing, Ingo; Jurkschat, Klaus
Abstract: The syntheses of the phosphonyl‐substituted ferrocenyl stannane Fe[ η 5 ‐C5 H3 ‐1‐SnPh3 ‐2‐P(O)(O‐ i Pr)2 η 5 ‐C5 H4 P(O)(O‐ i Pr)2 ] (1 ) and its iodine derivative Fe[ η 5 ‐C5 H3 ‐1‐SnPh2 I‐2‐P(O)(O‐ i Pr)2 η 5 ‐C5 H4 P(O)(O‐ i Pr)2 ] (2 ) are reported. The syntheses of the corresponding salts Fe[ η 5 ‐C5 H3 ‐1‐SnPh2 ‐2‐P(O)(O‐ i Pr)2 η 5 ‐C5 H4 P(O)(O‐ i Pr)2 ]X (3, X=AlOC(CF3 )3 4, 4, X=ClO4, 5, X=HgI3 ), respectively, are also described. The compounds are characterized by elemental analyses, 1 H, 13 C, 31 P, 119 Sn NMR and IR spectroscopy, electrospray ionization mass spectrometry, and, except for4 and5, single‐crystal X‐ray diffraction analyses. Abstract : Put your backbone into it ! Changing the Lewis acidity of the tin center on going from SnPh3 via SnIPh2 to SnPh2 + increases the strength of the intra‐ and intermolecular P=O→Sn coordination in the corresponding phosphonyl‐substituted ferrocene derivatives to the extent that a ferrocenyl‐backboned dinuclear dication, as its salt with the non‐coordinating aluminate anion [AlOC(CF3 )3 4 ] −, can be isolated.